The Effect of Using Picture Story Books On Speaking Ability Early Childhood: A Literature Review - Yona Sari; Tiara Fatrin; Ariyanti; Melinda (Lentera Perawat, 2025)
Development is the increase in abilities, structures and functions of the body that are more complex. One of the developments that is of concern is the development of speech. Some data show that the incidence of children who experience speech delays is quite high. The purpose of this study is to describe the use of picture story books on the speaking ability of early childhood children. This research is a qualitative study using the literature study method. The literature study method is a series of activities related to the method of collecting library data, reading and recording, and managing research materials. The results of the study after the author conducted a literature review of 5 journals that had been collected from various sources consisting of two (2) journals explaining the benefits and improvement of speaking ability from the use of picture story books and three (3) journals explaining the influence of story books on the development of speech in early childhood children showed a significant influence on improving the speaking ability of early childhood children after reading picture story books with good and correct intonation with greater frequency, children became more focused and learning was more interesting